Roles of circular RNAs in the pathogenesis and treatment of pancreatic cancer - Seimiya, Takahiro; Otsuka, Motoyuki; Fujishiro, Mitsuhiro (Frontiers in Cell and Developmental Biology, 2022)
Circular RNAs are single-stranded RNAs with a covalently closed structure formed by the process of back-splicing. Aberrant expression of circular RNAs contributes to the pathogenesis of a wide range of cancers. Pancreatic cancer is one of the most lethal cancers due to diagnostic difficulties and limited therapeutic options. Circular RNAs are emerging as novel diagnostic biomarkers and therapeutic targets for pancreatic cancer. Moreover, recent advances in the therapeutic application of engineered circular RNAs have provided a promising approach to overcoming pancreatic cancer. This review discusses the roles of circular RNAs in the pathogenesis of pancreatic cancer and in potential treatment applications and their usefulness as diagnostic biomarkers.